Kinetic acidity of supramolecular imidazolium salts - Effects of substituent, preorientation, and counterions on H/D exchange rates - Fahlbusch, Tilmann; Frank, Markus; Schatz, Jürgen; Schühle, Daniel T. (Journal of Organic Chemistry, 2006)
The deprotonation of imidazolium salts to N-heterocyclic carbenes is often a decisive step in modern catalytic reactions. Therefore, we studied the H/D exchange of the C H of 15 imidazolium-substituted calix[4]arenes and 11 nonmacrocyclic model compounds in methanol/water (97:3). The influence of the counterion, substitution directly on the imidazolium unit or on the preorientating calixarene backbone could be studied. The observed exchange rates might give a rational for the suitability of the imidazolium salts as precursors in the Suzuki coupling. © 2006 American Chemical Society.